Pengaruh Sumber Daya Manusia dan Inovasi Produk Terhadap Kinerja Kewirausahaan - Muttaqin, Arya Abdul Jabbar; Apriadi, Deri (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of Word of Mouth (WOM), brand image, and brand ambassador on consumer satisfaction with Le Minerale in Wonodadi District, Blitar Regency. A quantitative approach with a descriptive design was applied. The study involved 128 respondents selected through accidental sampling. The research instrument was a four-point Likert scale questionnaire tested for validity and reliability before use. Data were analyzed using SPSS version 27, including validity and reliability tests, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results show that WOM, brand image, and brand ambassador each have a positive and significant effect on consumer satisfaction. Simultaneously, these three variables also have a significant impact, with an R² value of 0.604, indicating that 60.4% of the variation in consumer satisfaction is explained by WOM, brand image, and brand ambassador, while the remaining 39.6% is influenced by other factors beyond this study. These findings highlight the importance of combining marketing communication strategies to enhance consumer satisfaction in the bottled drinking water industry.